PUBLIK RELATION DI ERA DIGITAL:PENGARUH TEKNOLOGI ARTIFICIAL INTELLIGENCE TERHADAP PRAKTIK PUBLIC RELATIONS MODERN - Rafi Prasojo (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
This study explores the impact of artificial intelligence (AI) on contemporary public relations (PR) practices. As technology advances, artificial intelligence (AI) has become a critical tool in public relations strategies, changing how organizations interact with the public. Artificial Intelligence (AI) enables routine tasks like sentiment analysis, media monitoring, and crisis management to be automatically completed, increasing communication efficiency and effectiveness. In addition, AI provides insights through large-scale data analysis, assisting PR professionals in crafting more intimate and personal campaign messaging. Despite this, implementing AI in PR can also cause problems, such as data security and e-commerce issues. This study highlights the benefits and challenges of using AI in PR, as well as its implications for the future of this profession. Research indicates that strategic AI integration can improve PR practices, but it also requires careful consideration and deliberation to maximize technological potential.